AN INTEGRATED METHOD FOR EVALUATING MANUFACTURING INDUSTRY STRATEGY MAP IN THE DIGITAL TRANSFORMATION ERA USING DEMATEL ANP AND BALANCED SCORECARD METHODS - Khamdani, Fatih; Alamsjah, Firdaus (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Digital transformation has played a pivotal role in shaping corporate strategies, influencing the selection of the most effective approaches to optimize benefits while minimizing the disruptive impact of technological change. This study aims to identify suitable digital transformation strategies within Indonesia’s textile and automotive manufacturing industries to support the country’s economic goals for 2030. The research methodology involves developing a strategy map and determining the most influential and prioritized strategic objectives through a quantitative approach, using interviews and questionnaires based on the Balanced Scorecard framework. The collected data is analyzed using DEMATEL and ANP techniques. The developed strategy map reveals that “Industrial Transformation 4.0” is the most influential strategic objective, while “Increasing Profitability” is identified as the top priority.